The analysis of low-dose glucocorticoid maintenance therapy in patients with primary nephrotic syndrome suffering from COVID-19 - Li, Yong-Qi; Wu, Min; Wang, Yu-Jia; Zhang, Yu-Xia; Lu, Jing; Zhao, Yi-Nan; Ji, Bo-Fan; Chen, Zhi-Qing; Tang, Ri-Ning; Liu, Bi-Cheng (Frontiers in Molecular Biosciences, 2024)
Objectives: This study aimed to describe the effects of low-dose (prednisolone acetate 2.5–7.5 mg/day) glucocorticoids (GCs) maintenance therapy in patients with primary nephrotic syndrome (NS) suffering from coronavirus disease 2019 (COVID-19). Methods: A single-center retrospective study of NS patients with COVID-19 infection in Zhongda Hospital Affiliated to Southeast University from 1 February 2022 to 31 March 2023 was conducted. All enrolled patients underwent renal biopsy for the pathological diagnosis and reached complete remission (CR) or near-CR before COVID-19 infection. According to the maintained therapy regimen, patients were divided into low-dose GCs group and non-GCs group. Results: A total of 125 patients were enrolled in the study. Their median age was 46.0 ± 15.6 years, and the median value of 24-h urine protein was 0.77 g. The majority of these patients received treatment for more than 6 months, with a significant portion achieving CR (29.6%) or near-CR (43.2%). The leading cause of NS was membranous nephropathy (52%). There were no significant differences in the baseline characteristics between low-dose GCs and non-GCs group. As compared to those in the non-GCs group, patients receiving low-dose GCs treatment showed less fatigue or muscle weakness, smell disorder, palpitations, decreased appetite, taste disorder, dizziness, sore throat or difficult to swallow and fever (p < 0.05). Moreover, patients in the low-dose GCs group were with higher median quality of life scores (85.0) than in the non-GCs group (p = 0.001). Further serum inflammatory factor analysis indicated that interleukin-6 (IL-6) levels in the non-GCs group were significantly higher than that in the low-dose GCs group (p < 0.05). Conclusion: Patients with NS in low-dose GCs maintenance therapy stage showed milder symptom, higher quality of life and decreased serum IL-6 levels compared to those, who were not on GCs maintenance therapy. These results suggest the beneficial effect of low-dose GCs therapy in NS patients with CR/near-CR suffering from COVID-19 infection.